The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3174/ajnr.a5992
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute Alcohol Consumption on the Human Brain: Diffusional Kurtosis Imaging and Arterial Spin-Labeling Study

Abstract: BACKGROUND AND PURPOSE: Brain function and microstructure are affected by alcohol consumption. Until recently, the effect of alcohol on neural mechanisms has not been fully elucidated. Our aim was to explore the acute effects of alcohol on healthy human brains by diffusional kurtosis imaging and 3D arterial spin-labeling and elucidate structural and functional changes in the brain on acute alcohol intake. MATERIALS AND METHODS:Conventional MR imaging, diffusional kurtosis imaging, and 3D arterial spin-labeling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The development of functional MR imaging technology has made it possible to visualize the change in the CBF using arterial spin-labeling (ASL) (without the use of contrast agents) because ASL can magnetize protons in the circulating blood as an endogenous perfusion tracer. 16,17 Several studies of neurologic diseases have shown a good correlation among ASL, DSC-perfusion MR imaging, and PET for evaluating the changes in CBF perfusion, and they support the credibility and feasibility of the clinical applications of ASL. [18][19][20][21] ASL can be used to identify the location of epileptic lesions, with the potential to replace interventional examinations.…”
mentioning
confidence: 88%
“…The development of functional MR imaging technology has made it possible to visualize the change in the CBF using arterial spin-labeling (ASL) (without the use of contrast agents) because ASL can magnetize protons in the circulating blood as an endogenous perfusion tracer. 16,17 Several studies of neurologic diseases have shown a good correlation among ASL, DSC-perfusion MR imaging, and PET for evaluating the changes in CBF perfusion, and they support the credibility and feasibility of the clinical applications of ASL. [18][19][20][21] ASL can be used to identify the location of epileptic lesions, with the potential to replace interventional examinations.…”
mentioning
confidence: 88%
“…A scalar index derived from DKI called the mean kurtosis (MK) measures the degree of diffusion restriction and indicates microstructural complexity (5). Indeed, its performance has been satisfactory and superior to that of diffusion tensor imaging (DTI) in identifying microstructural abnormalities in several cerebral pathologies, such as neonatal acute bilirubin encephalopathy (6), microstructural changes in brain regions upon acute alcohol intake (7), congenital sensorineural hearing loss (8), and BD (9). In a study on patients with BD, DKI could detect microstructural brain alterations in patients with BD and major depressive disorder (MDD) (10).…”
Section: Introductionmentioning
confidence: 99%
“…The traditional method used for clinical diagnosis of cerebral infarction relies on computed tomography (CT), which evaluates the absorption of different types of radiation by different tissues. However, some studies[ 5 - 7 ] have suggested that CT diagnosis and evaluation of cerebral infarction often cannot be performed within 6 h of onset, thus affecting the treatment.…”
Section: Discussionmentioning
confidence: 99%